Implementasi Program Al-Islam dan Kemuhammadiyahan dalam Pembinaan Akhlak Islami Siswa Kelas X di SMA Muhammadiyah Singaparna - Ahmad Faisal; Ayi Sobarna (UNISBA Press, 2022)
Abstract. Education must actually carry out the mission of islamic moral development so that students and graduates of educational institutions can participate in filling development well and succeed without leaving islamic moral values. One of the programs to improve Islamic morals that needs to be developed in the Islamic moral development program is the implementation of Al-Islam and Kemuhammadiyahan. Efforts to establish Islamic morals are also in line with the objectives of National education as stated in the National Education Law No. 20 of 2003 Article 3. The purpose of this study is to identify the management of the implementation of the Al-Islam and Kemuhammadiyahan programs in the development of Islamic morals at Muhammadiyah Singaparna High School in the form of planning, implementation, and evaluation. The research method used is descriptive analytic with a qualitative approach. The data collection techniques used are in the form of interviews, field observations (observations), and documentation studies. The results of this study show that: (1) Planning for the implementation of the Al-Islam and Kemuhammadiyahan programs in the development of Islamic morals has not had careful planning, the implementation of the Al-Islam and Kemuhammadiyahan Programs refers to the vision of school schools, namely to create superior graduates, entrepreneurial abilities based on leadership spirit and noble morals. Through this program, it is hoped that students will have faith and devotion to Allah SWT, have a noble character, as well as have a good personality according to Indonesian norms and culture (2) Implementation of the implementation of the Al-Islam and Kemuhammadiyahan programs through three activities; a) Malam Bina Iman dan Taqwa (MABIT), b) Extracurricular Tahfidz and c) Islamic Competition d) recitation of educators. (3) Evaluation of activities shall be carried out through the Principal, Coach and person in charge of the activity. Abstrak. Pendidikan sejatinya harus mengemban misi pembinaan akhlak yang islami sehingga peserta didik dan para lulusan lembaga pendidikan dapat berpartisipasi dalam mengisi pembangunan dengan baik dan berhasil tanpa meninggalkan nilai-nilai akhlak islami. Salah satu program untuk meningkatkan akhlak islami yang perlu dikembangkan dalam program pembinaan akhlak islami adalah implementasi Al-Islam dan Kemuhammadiyahan. upaya pembentukan akhlak islami juga selaras dengan tujuan pendidikan Nasional seperti tercantum dalam UU Sisdiknas No. 20 Tahun 2003 Pasal 3. Tujuan dari penelitian ini adalah untuk mengidentifikasi pengelolaan implementasi program Al-Islam dan Kemuhammadiyahan dalam pembinaan akhlak islami di SMA Muhammadiyah Singaparna dalam bentuk perencanaan, pelaksanaan, dan evaluasi. Metode penelitian yang digunakan adalah deskriptif analitik dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan berupa wawancara, observasi lapangan (pengamatan), dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa: (1) Perencanaan implementasi program Al-Islam dan Kemuhammadiyahan dalam pembinaan akhlak islami belum memiliki perencanaan yang matang, implementasi Program Al-Islam dan Kemuhammadiyahan mengacu pada visi sekolah sekolah yaitu untuk terciptanya lulusan yang unggul, berkemampuan wirausaha dilandasi jiwa kepemimpinan dan akhlak mulia. Melalui program ini diharapkan siswa memiliki keimanan dan ketaqwaan kepada Allah SWT, berakhlak mulia, sekaligus memiliki kepribadian yang baik sesuai norma dan budaya Indonesia (2) Pelaksanaan implementasi program Al-Islam dan Kemuhammadiyahan melalui tiga kegiatan; a) Malam Bina Iman dan Taqwa (MABIT), b) Ekstrakulikuler Tahfidz dan c) Lomba Islami d) pengajian tenaga pendidik. (3) Evaluasi kegiatan dilakukan melalui Kepala Sekolah, Pembina dan penanggung jawab kegiatan.